2020
DOI: 10.1108/ejm-02-2018-0129
|View full text |Cite
|
Sign up to set email alerts
|

Promotional phrases as analogical questions: inferential fluency and persuasion

Abstract: Purpose As an alternative to straight rhetorical questions, questions using analogies that invite the reader to think about the frame of reference to answer the target have been used in advertising to persuade. This paper aims to investigate consumer responses to the use of analogical questions in ads for incrementally new products and the important variables moderating those responses. Design/methodology/approach Four between-subjects experiments examined how product evaluations in response to analogical qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Consistent with other studies on persuasion knowledge (e.g. Isaac & Grayson, 2017Kim et al, 2016;Ku & Chen, 2020;Seo et al, 2019), we have shown that, in the domain of advertising, increased levels of scepticism lead to higher trustworthiness and, therefore, to higher evaluations of a more credible (two-sided message) relative to a less credible tactic (one-sided message). However, these effects occur only beyond a certain threshold level; below this level, the effect of message sidedness is not significant.…”
Section: Theoretical Contributionssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with other studies on persuasion knowledge (e.g. Isaac & Grayson, 2017Kim et al, 2016;Ku & Chen, 2020;Seo et al, 2019), we have shown that, in the domain of advertising, increased levels of scepticism lead to higher trustworthiness and, therefore, to higher evaluations of a more credible (two-sided message) relative to a less credible tactic (one-sided message). However, these effects occur only beyond a certain threshold level; below this level, the effect of message sidedness is not significant.…”
Section: Theoretical Contributionssupporting
confidence: 91%
“…Past research has shown support for Friestad and Wright's (1994) proposition. Responses to marketing stimuli are more distinctive among people with higher (vs. lower) persuasion knowledge, or when people are primed to access persuasion knowledge (Isaac & Grayson, 2017, 2020; Forehand & Grier, 2003; Bambauer‐Sachse & Mangold, 2013; Hamby & Brinberg, 2018; Kim et al, 2016; Ku & Chen, 2020; Lim et al, 2020; Morales, 2005; Seo et al, 2019; Wei et al, 2008). Therefore, more persuasion knowledge increases the ability to distinguish honest from deceitful marketing practices.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…and maximize the internal validity of the study (Lanseng and Olsen, 2012; Newmeyer and Ruth, 2020). Further, such an approach helps eliminate brand familiarity effects that might have a confounding effect on the dependent variable (Ku and Chen, 2020; Lieven et al , 2015). The length of the reviews and responses has had an impact on consumer perceptions such as information diagnosticity and review helpfulness thereby affecting review readers’ perceptions (Karimi and Wang, 2017; Mudambi and Schuff, 2010; Pan and Zhang, 2011; Qazi et al , 2016; Salehan and Kim, 2016; Zhou and Guo, 2017) and reviewer behavior (Chen and Huang, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Consumer researchers have explored how rhetorical queries, those designed with an implied answer, and their tag variants impact persuasion (Ahluwalia & Burnkrant, 2004; Burnkrant & Howard, 1984; Chang, 2011; Howard, 1990; Munch & Swasy, 1988; Petty et al, 1981; Swasy & Munch, 1985). Alternative phrasings to persuade, such as directive questions and concession questions (Areni, 2003), hypothetical questions (Fitzsimons & Shiv, 2001), analogical questions (Ku & Chen, 2020), and problem‐focused and benefit‐focused questions (Ku et al, 2019), have also been addressed.…”
Section: Introductionmentioning
confidence: 99%